Gendered bodies, fractured nations: Feminist resistance and the politics of representation in contemporary Anglophone fiction - Khan, Aayesha Sagir; Saleh, Shoeb; AlAli, Rommel Mahmoud; Abdullatif, Ali (Research Journal in Advanced Humanities, 2026)
This article argues that contemporary Anglophone fiction does not treat the gendered body as a passive metaphor for national crisis; rather, it stages embodiment as the material and narrative interface through which nation, violence, citizenship, memory, and dissent become legible. Reading Chimamanda Ngozi Adichie’s Americanah, Kamila Shamsie’s Home Fire, Arundhati Roy’s The Ministry of Utmost Happiness, and Tsitsi Dangarembga’s This Mournable Body comparatively, the essay shows how women’s bodies, queer and trans bodies, and feminized subjectivities are made to bear the pressure of fractured national projects. Hair, dress, grief, sexuality, mobility, and bodily exhaustion emerge as techniques through which states and publics sort subjects into the visible and invisible, the grievable and disposable, the assimilable and suspect. Drawing on feminist literary criticism, postcolonial feminism, intersectionality, and biopolitical thought, the essay combines close reading with comparative analysis to demonstrate that these novels resist both nationalist romance and liberal narratives of individual empowerment. Their formal strategies—blogging, tragic refunctioning, polyphony, and second-person estrangement—render embodied precarity neither merely private nor simply symbolic. Instead, they expose how intimate life is governed by public power while also imagining insurgent forms of relation and survival.